MUAY THAI EXERCISE'S IMPACT ON BODY SATISFACTION AND SELF-ESTEEM IN WOMEN - Asmawi, Muhammad Agung; Hartoko, Rahadi Arie; Tihardimanto, Andi; Arief, Ariyanto; Damis, Rahmi (HEARTY, 2025)
With the increasing popularity of Muaythai martial arts in improving physical fitness, understanding the impact this type of sport has on mental health is imperative. In most countries around the world, women are the gender most at risk of experiencing low levels of Bodysatisfaction and self esteem. Objectives: This study focused on the relationship of Muaythai training with Bodysatisfaction and Self-Esteem in adult women. Methods: This study used a cross-sectional approach and was conducted on 43 adult women who were determined through the total sampling method. This study was conducted in January 2024 - February 2024 at Bintang Muaythai Camp Makassar. Data analysis was performed univariately and bivariately using Spearman's rank correlation test. Results: The correlation between variables was analyzed using Spearman's rank correlation test and there was no significant relationship between Muaythai training and Bodysatisfaction in adult women (p-value; 0.716), and there was no relationship between Muaythai training and Self-Esteem in adult women (p-value; 0.340).